2018
DOI: 10.3390/su10072568
|View full text |Cite
|
Sign up to set email alerts
|

ICT Development and Sustainable Energy Consumption: A Perspective of Energy Productivity

Abstract: Abstract:The information and communication technology (ICT) is closely related to the future of global energy consumption, not only because the ICT equipment itself increasingly consumes energy, but also because it is a general-purpose technology which may affect energy use of almost all sectors. Given the controversy over the net energy-saving effect of ICT, this paper focuses on a new perspective, i.e., energy productivity, to investigate the relationship between ICT development and energy consumption. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 57 publications
4
29
0
Order By: Relevance
“…Results of the study confirm the research of Yan et al (2018), who identified a positive impact of ICT development on energy productivity. The analysis provides a different perspective on this relation by analyzing the aspects that determine a developed ICT sector and can contribute to a higher energy productivity.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Results of the study confirm the research of Yan et al (2018), who identified a positive impact of ICT development on energy productivity. The analysis provides a different perspective on this relation by analyzing the aspects that determine a developed ICT sector and can contribute to a higher energy productivity.…”
Section: Discussionsupporting
confidence: 85%
“…The positive influence on energy productivity provided by Pillar 6, ICT individual usage, which includes indicators related to internet usage and internet infrastructure in its computation, as well as the influence of Pillar 7, business usage, which includes indicators such as business-to-consumer internet use and firm-level absorption, suggests an alignment with the conclusion of Romm et al (2008), who identified that the internet can help lower electricity intensity. The influence that ICT usage and its impact on the economy have on energy productivity also confirms the results of Yan et al (2018), which showed a positive relation between ICT development and energy productivity. However, a closer analysis of the indicators that make up these pillars needs to be carried out.…”
Section: Results Of the Panel Data Analysis With Random Effectsupporting
confidence: 78%
See 1 more Smart Citation
“…Energy saving is a global issue today. It is needed a strategy to save the energy for operating the ICT business include wireless technology [12], rather than debating what kind of technology that saves the energy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Energy saving is a global issue today. It is needed a strategy to save the energy for operating the ICT business include wireless technology [12], rather than debating what kind of technology that saves the energy [13].Power consumption of network devices does not have any relation with the bandwidth condition, but it has relationship with the configuration of the device [14]. The network device configuration includes how data forwarded, the size of the packet, and what operation mode the device to be.…”
mentioning
confidence: 99%